Disability and Religious Diversity - Schumm, D. author. aut Link
XX, 234 p.
Keywords: This collection of essays examines how diverse religions of the world represent, understand, theologize, theorize and respond to disability and chronic illness. Contributors employ a variety of methodological approaches including ethnography, historical, cultural, or textual analysis, personal narrative, and theological/philosophical investigation.